Effects of three processing technologies on the structure and immunoreactivity of α-tropomyosin from Haliotis discus hannai. (30th March 2023) - Ji, Nairu; Yu, Chenchen; Han, Xinyu; He, Xinrong; Kang, Shuai; Bai, Tianliang; Liu, Hong; Chen, Guixia; Cao, Minjie; Liu, Guangming
Graphical abstract: Highlight: 1. Three processing technologies converted α-helix to β-sheet, β-turn, and random coil. 2. Glycation of TM by xylose reduced the immunoreactivity mostly. 3. Glycation of TM could modify-two epitopes by three N-glycated sites. Abstract: The subunit of tropomyosin (α-TM) from Haliotis discus hannai is an important allergen. The methods to reduce the immunoreactivity of α-TM are worth investigating. Thus, this study confirmed the reacted conditions of α-TM with transglutaminase (TG)-catalyzed cross-linking reaction, TG-catalyzed glycosylation, and glycation. Three processing technologies reduced significantly the contents of α-helix and hydrophobic force of α-TM and increased the surface hydrophobicity. A serological experiment confirmed that the glycated α-TM with xylose showed the lowest IgG/IgE-binding capacity. The inhabitation dot blot displayed that five epitope peptides could bind with the site-specific IgE prepared by the glycated α-TM. Three in nine glycated sites (M68, N202, and N203) were verified to modify-two epitopes (L-HTM-3 and L-HTM-7) of α-TM, which affected the immunoreactivity of α-TM during glycation. These results indicated that glycation would be desired for developing hypo-allergenic abalone products.